Being a Special Education Teacher in a General Education School: Effect of Working Conditions on Work Alienation - Sinem Canpolat; Meltem Sünkür Çakmak (Ankara Üniversitesi Eğitim Bilimleri Fakültesi Özel Eğitim Dergisi)
Introduction: The purpose of this study is to find the effect of working conditions of special education teachers, who work in general education schools, on the work alienation levels. The issues that differentiate the working conditions of special education classes from others are various special conditions, such as the way break times are used, the requirement to have two teachers in a class and the needs to have special physical materials and arrangements.Method: Phenomenology pattern, one of qualitative research methods, was used in the study. Study data were collected through semi-structured interview technique and the data were analyzed through descriptive analysis technique. 20 special education teachers working in the city center of Diyarbakır during 2019-2020 academic year participated in the study. The study group was determined through snowball and criterion sampling methods.Findings: When the study findings were examined, it was found that the teachers have intensive amount of work alienation. It can be claimed that special education teachers are experiencing alienation in isolation level at most and senselessness level at least. It was concluded that working conditions have an effect on work alienation of special education teachers. Discussion: It is understood that special education teachers feel themselves unhappy, alone and isolated in the organizations they work, they are required to work in an environment, where no one understands them, they believe that they will not receive the support they need from their managers, they experience a conflict of authority within the class and they have problems in following the rules of organization. Thus, it was found that they experience many symptoms of work alienation. It is recommended to hire supporting staff to takeover the responsibility of care of students from these teachers and ensure that special education teachers work under the same conditions with their colleagues.